The Opinions of Health Professionals in Maternity Clinics on Perinatal Loss and Lament - Pelin PALAS KARACA; Yeliz KAYA; Sevde AKSU (Yaşam Becerileri Psikoloji Dergisi, 2020)
This is a descriptive study. It was carried out to determine the opinions of health professionals about “Perinatal Loss and Lamentation”. The study was conducted with the midwives and nurses working in a maternity and neonatal clinics in a public hospital and a city hospital between September 2019 and November 2019. The sample of the study consisted of 52 health professionals who accepted to participate in the study and filled the data collection form. The data of the study were collected with “Personal Information Form” and “Opinions on Perinatal Loss and Mourning Form”. Mann-Whitney U test and Kruskal-Wallis H test were used to evaluate the data.In the study, it was determined that all of the midwives and nurses were women (100%), almost all of them were married (90.4%) and more than half of them were nurses (69.2%). It was determined that 5.8% of them were high school graduates, 19.2% of them had an associate degree, 71.2% of them had a bachelor degree and 3.8% of them had a graduate diploma. It has been found that the midwives and nurses' highest working year was more than 20 years. When the pregnancy losses before the graduation and the status of receiving education about perinatal mourning were examined, nearly half of the midwives and nurses received the training (46.2%) and the participants stated that the training received was partially sufficient (32.7%). In the study, The statements of “Perinatal loss covers early/late fetal and neonatal deaths”, “After perinatal loss, parents may experience a mourning period”and, “Perinatal loss may negatively affect the physical health of the woman”, “Perinatal loss may negatively affect the psycho-social health of the woman”, “Parents experiencing perinatal loss should be encouraged by healthcare professionals to express their feelings” were most shared ones by the participants. In the study, it was determined that the mean score of the midwives and nurses on the OPLMF was 39.69 ± 5.65 and the scores ranged between 26-51. It was determined that the midwives and nurses had moderate knowledge of perinatal loss and mourning.